Bioinspired soft nanovesicles for site-selective cancer imaging and targeted therapies - Prasad, Rajendra (2022)
Funding Information: European Research Council, ERC Starting Grant, Grant/Award Number: ERC‐StG‐2019‐848325 Funding information Funding Information: This work is supported by the European Research Council, ERC Starting Grant ‐ ERC‐StG‐2019‐848325. The authors would like to thank Dr. N. K. Jain, Dr. S. Meena, and Dr. Gorain for glancing at this article. We would like to dedicate this article to the memory of late Prof. Sanjiv Sam Gambhir, a molecular imaging and early cancer detection scientist. We have cited all reproduced images and figures in this review. Publisher Copyright: © 2022 Wiley Periodicals LLC.